Evaluation of Financial Sustainability of the Federal Health Institutions in Nigeria - Odewole, Philip Olawale; Salawu, Mary Kehinde; Salawu, Rafiu Oyesola (European Journal of Sustainable Development, 2021)
The study investigated the financial sustainability of the federal health institutions in Nigeria. The population of the study comprised twenty-five (25) federal health institutions from four (4) geo-political zones and Abuja. Secondary data were sourced from Annual General Warrant from the Office of the Accountant General of the Federation and Audited Financial Statements of the Public Sector Entities. Data obtained were analyzed using Balanced Score Card techniques. The results showed that none of the sampled federal health institutions in Nigeria attained a basic standard of sustainability test, whereby the ratios of their Internally Generated Revenue to recurrent expenditure is between (40 – 60)% or 0.04 and 0.6.This indicates the inability of the institutions to generate sufficient revenue independently to cover even the operational expenses in the short-run. Also, the results equally showed the highest positive operating surplus ratios of 1%-5% of operational sustainability indicating that the health institutions heavily depended on central authority’s funding for their survival. The results further revealed that none of the federal health institutions attained both intermediate and advance standards of sustainability tests. In conclusion, federal health institutions in Nigeria are heavily dependent on central authority for sustenance. Therefore, the central authorities should roll out blueprints that will make the institutions widen their internally generated revenue capacity and reduce the reliance on central authority’s funding for survival.